Answered

Find the best answers to your questions at Westonci.ca, where experts and enthusiasts provide accurate, reliable information. Get quick and reliable solutions to your questions from a community of experienced experts on our platform. Our platform provides a seamless experience for finding reliable answers from a network of experienced professionals.

What is a simplified expression for (x−y)−(x+y)?

Sagot :

Answer:

-2y

Step-by-step explanation:

Let's simplify step-by-step.

x−y−(x+y)

Distribute the Negative Sign:

=x−y+−1(x+y)

=x+−y+−1x+−1y

=x+−y+−x+−y

Combine Like Terms:

=x+−y+−x+−y

=(x+−x)+(−y+−y)

=−2y

Answer:

-2y

Step-by-step explanation:

............... ..........